Pola Permukiman Tradisional Kajang - Erni Erawati (Balai Arkeologi Maluku, 2016)
One of traditional settlements in Indonesia is located in the residential area of Kajang, Bulukumba, South Sulawesi Province. Settlement community in Kajang is classified into two levels, the first is meso level consisted on spatial villaes, homes, and forest, and the second is macro level consisted on the spatial region consisting of kamase-masea region, and the region kuassayya. From the shape and function of artefacts and sites in Kajang area, it can be mentioned that the Kajang district has the Megalithic sites and Islamic sites which are still functioned until recently. The aim of this research is determining the pattern of settlement in the area of the Kajang based on the location of the sites. The source of data consist of two namely secondary data which is obtained from literary research, and primary data obtained through field research by observation and survey. The pattern of settlement in the Kajang area shows two characteristics; firstly, Settlement patterns and placement of home in group, leading to the altitude, facing to the west; the sacred building that is located at high altitude and surrounded by indigenous forest areas and settlers' houses. Secondly, settlement patterns extend lengthwise in a row on both sides of a pathway up to the foothills, and on riverbanks. Those houses are characterised by the location of owner's social stratification. There is no specific orientation of houses to the wind directions. Sacred building is placed in higher space surrounded by residents' houses. Ammatoa as the spiritual leader, and a site that functions to inaugurate Karaeng as leaders of the governance. Salah satu permukiman tradisional di Indonesia adalah permukiman di kawasan Kajang, Kabupaten Bulukumba, Propinsi Sulawesi Selatan. Permukiman masyarakat di kawasan Kajang terdiri atas dua tingkat, yaitu bersifat meso yang menyangkut tata ruang desa, rumah tinggal, dan hutan adat, dan bersifat makro menyangkut tata ruang kawasan yang terdiri atas kawasan kamase-masea dan kawasan kuassayyya. Dari bentuk dan fungsi situs-situs di kawasan Kajang, dapat dikatakan bahwa kawasan Kajang memiliki situs Megalitik dan situs Islam yang masih dipergunakan sampai sekarang. Penelitian bertujuan untuk mengetahui pola permukiman di Kawasan Kajang berdasarkan letak situs-situs. Sumber data penelitian ada dua, yaitu data sekunder yang diperoleh melalui penelitian pustaka, dan data primer diperoleh melalui penelitian lapangan dengan cara observasi dan survei permukaan.Pola permukiman di kawasan Kajang menampilkan dua ciri, yaitu: 1). Pola permukiman dan penempatan rumah secara berkelompok mengarah pada ketinggian, arah hadap rumah ke arah barat, bangunan sakral berada di tempat ketinggian dan dikelilingi oleh kawasan hutan adat dan bangunan rumah penduduk, 2). Pola permukiman berbentuk memanjang dan berderet disebelah menyebelah jalan, kaki bukit, dan pinggir sungai dan pantai dengan ciri yang menunjukkan pelapisan sosial. Terdapat dua fungsi situs di kawasan Kajang, yaitu: situs yang berfungsi sebagai tempat pelantikan Ammatoa sebagai pemimpin di bidang spiritual, dan tempat pelantikan Karaeng yang dianggap pemimpin di bidang pemerintahan.